Leveling program for the improvement of the oral production ability of the English language in students of the 1st cycle of translation and interpretation Academic Professional School. César Vallejo University, Chiclayo - Torres Vargas, Esdras Joel (2018)
The levelling program in heterogenic groups, has been elaborated taking into account the measures of the scientific methodology and it is oriented to better the oral production ability in the English language from the students in the first cycle of the Professional Academic School of Translation and Interpretation at César Vallejo University in Chi-clayo. Nowadays in the Professional Academic School of Translation and Interpretation exists a great interest for developing and better the level of knowledge of the English language, however the oral production ability, which is considered by the author an ability necessary and important to work in the acquisition of this language, remains of a big difficulty because many times this ability has not given the priority for teachers and students. In this research was formulated the problem of investigation, the hypothesis, the general objective and the specific objectives. The kind of research is quantitative and the design is in the quasi experimental level. The research was done with a group of 33 students from the first cycle of translation and interpretation. During the research a leveling program for heterogene-ous group has been developed, which contains learning sessions that have been developed in such way that answers the student´s needs and has like the main approach, the communicative approach.